Intergenomic interactions between mitochondrial and Y‐linked genes shape male mating patterns and fertility in Drosophila melanogaster. (16th October 2015) - Yee, Winston K.W.; Rogell, Björn; Lemos, Bernardo; Dowling, Damian K.
Abstract : Under maternal inheritance, mitochondrial genomes are prone to accumulate mutations that exhibit male‐biased effects. Such mutations should, however, place selection on the nuclear genome for modifier adaptations that mitigate mitochondrial‐incurred male harm. One gene region that might harbor such modifiers is the Y‐chromosome, given the abundance of Y‐linked variation for male fertility, and because Y‐linked modifiers would not exert antagonistic effects in females because they would be found only in males. Recent studies in Drosophila revealed a set of nuclear genes whose expression is sensitive to allelic variation among mtDNA‐ and Y‐haplotypes, suggesting these genes might be entwined in evolutionary conflict between mtDNA and Y. Here, we test whether genetic variation across mtDNA and Y haplotypes, sourced from three disjunct populations, interacts to affect male mating patterns and fertility across 10 days of early life in D. melanogaster . We also investigate whether coevolved mito‐Y combinations outperform their evolutionarily novel counterparts, as predicted if the interacting Y‐linked variance is comprised of modifier adaptations. Although we found no evidence that coevolved mito‐Y combinations outperformed their novel counterparts, interactions between mtDNA and Y‐chromosomes affected male mating patterns. These interactions were dependent on male age; thus male reproductive success was shaped by G × G × E interactions.